2020
DOI: 10.1177/1534735420924466
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Perceptions to Prehabilitation in Lung Cancer

Abstract: Background: Prehabilitation to maximize exercise capacity before lung cancer surgery has the potential to improve operative tolerability and patient outcomes. However, translation of this evidence into clinical practice is limited. Aims: To determine the acceptability and perceived benefit of prehabilitation in lung cancer among thoracic surgeons. Procedure: 198 cardiothoracic surgeons within Australia and New Zealand were surveyed to evaluate their attitudes and perceived benefits of prehabilitation in lung c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Our study identified a number of potential barriers to the implementation of exercise into routine lung cancer care, some of which have been identified previously in the literature, including clinician knowledge, workplace culture, constraints of the health care system (e.g., clinician time, staffing, and protocols), and patient appointment burden [ 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study identified a number of potential barriers to the implementation of exercise into routine lung cancer care, some of which have been identified previously in the literature, including clinician knowledge, workplace culture, constraints of the health care system (e.g., clinician time, staffing, and protocols), and patient appointment burden [ 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…This challenge is not unique to the UK; a recent survey of thoracic surgeons in Australia identified a high perceived need for prehabilitation, but only 16.7% of respondents could access services. 13 The Greater Manchester (GM) Prehab4Cancer (P4C) programme is a system-wide prehabilitation programme for patients in GM delivered as a collaboration between hospitalbased clinical teams, the regional cancer alliance (GM Cancer), and the community leisure sector (GM Active). Here, we examine the feasibility, uptake, participation, and clinical outcomes from this service delivery model.…”
Section: Editor's Key Pointsmentioning
confidence: 99%
“…This challenge is not unique to the UK; a recent survey of thoracic surgeons in Australia identified a high perceived need for prehabilitation, but only 16.7% of respondents could access services. 13 …”
mentioning
confidence: 99%
“…However, implementation of prehabilitation remains a challenge. Despite evidence of effectiveness, barriers include access to specialized services, lack of awareness as to which patients need referrals, and resource limitations . Physically integrating the prehabilitation platform into an existing preoperative clinic represents an opportunity to address implementation barriers, shifting the role of the preoperative clinic paradigm from risk assessment to risk attenuation where at-risk patients are offered a tailored prehabilitation plan that is designed and delivered seamlessly and on site (Figure).…”
Section: What Is the Innovation?mentioning
confidence: 99%